2011
DOI: 10.1108/07363761111181509
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic symbolism and children's brand name preferences

Abstract: Purpose -Children are bombarded by branded communication every day. The purpose of this paper is to investigate the role that particular linguistic devices play in communication, and whether this process differs between children and adults. One such device is phonetic symbolism, which has been shown to lead adults to prefer brand names whose phonetic attributes match product and/or brand features. Design/methodology/approach -Three experiments were undertaken to examine children's (six to 12 years of age) pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 15 publications
0
32
0
2
Order By: Relevance
“…This concept has long been discussed in linguistics literature (Sapir, 1929;Ohala, 1984;Hinton et al, 1994). Recent research in marketing has adopted the concept of sound symbolism from the field of linguistics (Klink, 2000(Klink, , 2001Lowrey and Shrum, 2007;Baxter and Lowrey, 2011;Shrum et al, 2012;Kuehnl and Mantau, 2013;Wu et al, 2013). Sound symbolism is a linguistic process in which the sounds of a word provide cues about the word's meaning (Yorkston and Menon, 2004).…”
Section: Brand Name Classification Frameworkmentioning
confidence: 97%
“…This concept has long been discussed in linguistics literature (Sapir, 1929;Ohala, 1984;Hinton et al, 1994). Recent research in marketing has adopted the concept of sound symbolism from the field of linguistics (Klink, 2000(Klink, , 2001Lowrey and Shrum, 2007;Baxter and Lowrey, 2011;Shrum et al, 2012;Kuehnl and Mantau, 2013;Wu et al, 2013). Sound symbolism is a linguistic process in which the sounds of a word provide cues about the word's meaning (Yorkston and Menon, 2004).…”
Section: Brand Name Classification Frameworkmentioning
confidence: 97%
“…However, if they are learned over time, then shared meanings that frequently differ across cultures suggest that the effects may not be cross‐culturally robust and are unlikely to be observed at the earliest stages of language development (cf. Baxter & Lowrey, , ).…”
Section: Framework Applicationmentioning
confidence: 99%
“…In recent years, researchers have suggested that developmental factors impact the presence of phonetic symbolism effects (Baxter and Lowrey, 2011. Phonetic symbolism effects manifest as children age and develop the necessary language-based skills and knowledge (for example, phonological awareness; Fowler, 1991) .…”
Section: Sound Symbolism In Brand Names: the Moderating Role Of Agementioning
confidence: 99%